Contribution of physical health, sense of personal agency, and use of social media on the psychological well-being of government internal auditors: Kontribusi kesehatan fisik, sense of personal agency dan penggunaan media sosial terhadap psychological well-being auditor internal pemerintah - Sri Andayani; Putri Aisyah Naurasari (Talenta Publisher, 2023)
The crisis due to the Covid-19 pandemic has harmed the community's physical health, psychological and social well-being. This study aimed to determine the effect of physical health, sense of personal agency, and use of social media on PWB in government internal auditors. The design used in this study is a quantitative correlational approach. This study's results indicate an influence between physical health and a sense of personal agency on PWB in internal government auditors. Physical health affects 23%, while the sense of personal agency is 72%. By calculating all the biopsychosocial model variables, it can be concluded that the sense of personal agency has a more significant influence on PWB than physical health and the use of social media on internal government auditors.